PENGARUH PEMAHAMAN AGAMA, MOTIFASI MENDAPATKAN PROFIT DAN TINGKAT PENDIDIKAAN TERHADAP KESADARAN SERTIFIKASI HALAL BAGI PRODUSEN MAKANAN DI KABUPATEN SLEMAN DAN BANTUL - Waluyo Waluyo (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2013)
This research aims to determine whether there is an understanding of the influence of religion, profit motivation and education levels of the awareness of certified halal food for producers in Sleman and Bantul, as well as to find among the independent variables which are more significant. This research is a quantitative study with multiple regression analysis. Independent variables (religious understanding, motivation and profit levels) simul-taneously have significant effect on awareness of halal certification for food producers in Sleman and Bantul with the amount of influence of 66.7%. The independent variables that have a significant effect on the dependent variable  (motivation of certified halal) is understanding of religion variable and profit motivation.